A management approach for secondary shoulder and forearm deformities following obstetrical brachial plexus injury - Price, A E; Grossman, J A (Hand clinics, 1995)
This article provides an overview of the historical perspectives of shoulder deformity. Biomechanical considerations are discussed, as well as the authors' personal approach to these types of injuries.